Respuesta :

[tex]f(x) = ab^x~\hfill \begin{array}{llll}\textit{we know that}~f(0)=-4\begin{cases}x=0\\f(x)=-4\end{cases}\\\\-4=ab^0\implies -4=a(1)\implies -4=a\end{array}\\\\\\\stackrel{therefore}{f(x)=-4b^x}~\hfill \textit{we also know that}~f(-2)=-64\begin{cases}x=-2\\f(x)=-64\end{cases}[/tex]

[tex]-64=-4b^{-2}\implies \cfrac{-64}{-4}=b^{-2}\implies 16=b^{-2}\implies 16=\cfrac{1}{b^2} \\\\\\ b^2=\cfrac{1}{16}\implies b=\sqrt{\cfrac{1}{16}}\implies b = \cfrac{\sqrt{1}}{\sqrt{16}}\implies b = \cfrac{1}{4} \\\\[-0.35em] ~\dotfill\\\\ ~\hfill f(x)=-4\left( \frac{1}{4} \right)^x~\hfill[/tex]